Whaling ships's journals - Margaret (Whaling ship); York (Whaling ship)
One volume containing a journal (1838-1839) and logbook (1840) kept during a voyage of the whaling ship Margaret under master, Theodore Wimpenny, of Newport, R.I., from whaling grounds in the Pacific Ocean; and a journal (1841-1842) written during a voyage of the whaling ship York under master, Pease (forename unknown), of Edgartown, Mass., to whaling grounds on the Northwest Coast. Includes newspaper clippings and jottings removed from volume.
Collection material in English.
Keywords: Pease -- (Whaling master); Wimpenny, Theodore; Logbooks; Ship's papers -- 19th century; Voyages to the Pacific coast; Whalers (Persons); Whaling -- Massachusetts -- Edgartown; Whaling -- Rhode Island -- Newport; Whaling -- Pacific Ocean